A NOVEL NETWORK ANALYZING TOOL (NNAT) FOR COMPLEX NETWORK INFORMATION VISUALIZATION - ISMAIL, ASMA BARZHAWAND; SABR , ROZHGAR RZGAR; SHAIKHAH, SALAR KHEDER (Journal of Duhok University, 2023)
Analyzing and monitoring networks can be difficult, especially when large volumes of packets fly back and forth between devices. Therefore, visual network analysis provides a solution by allowing users to visualize and interpret complex network data more intuitively and interactively. Traditional tools have limited visualization capabilities and mostly represent data in a tabular format that is difficult to analyze and time-consuming for the users. In this paper, a novel network analyzing tool (NNAT) is proposed to integrate packet sniffing, visual analysis of packets, and live network scanning within the same tool. Also, presenting the analyzed data via different interfaces with the capability of filtering specific information. The function variety of the proposed tool reduces the number of tools to be used by network admins. Also, the flexibility of the proposed tool in the data visualization and presentation with proper diagrams and drawings makes it to be user-friendly, in additional to its inherent outperformance explore and analyze large datasets compared to traditional tools.